Experimental substantiation of combined fixation of tumor endoprothesis for the replacement of diaphyseal defects of rat long bones - Vyrva, Oleg; Mikhanovsky, Dmytro; Golovina, Yanina; Nikolchenko, Olga; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Goal: to compare the durability of fixation of endoprothesis for replacement of postresection femur defects in experimental animals under bending and strain loading. Methods: investigation was performed on 20 non-linear white rats at the age of 6 months. Partial resection of femur middle 1/3 and defect replacement with modular endoprothesis was performed. Average diameter and lenght of intramedullary canal of rat femur were defined using radiographic and osteometrtic investigation of the rats of analogous age, gender and body-weight. The sizes of intramedullary stems for fixation of endoprothesis in bone canals were claculated using obtained data. Plate was fixed with screws to the body of endoprothesis and after implantation it adjoined tightly to distal femur fragment. Intramedullary stems and plate were covered with a layer of corundum ceramics. The animals were devided on 2 groups: experimental group — using of modular endoprtohesis with plate; control group — using of modular endoprtohesis without plate. 3 months after operation the durability of endoprothesis fixation to bone diaphysis were studied under bending and strain loading. Results: control group — just in 3 rats of 10 the stable fixation of endoprothesis was observed. According to index of bending moment the best results were revealed for intact femurs — (1,89 ± 0,81) N•m. Conclusion: use of endoprothesis with additional plate fixation allowed to obtain more durable fixation «implant-bone» and significantly decreased the quantity of postoperative complictions.